2013
DOI: 10.5152/akd.2013.106
|View full text |Cite
|
Sign up to set email alerts
|

Increased apolipoprotein A-I levels mediate the development of prehypertension among Turks

Abstract: Objective: We aimed to assess whether apolipoprotein (apo) A-I levels that generated type-2 diabetes and coronary disease among Turks contribute to prehypertension and hypertension. Methods: A population-based sample of 2207 adults (mean age 53±11 years) was studied prospectively over a 6.5 years' follow-up. Individuals with hypertension and/or prehypertension were excluded at baseline. Results: At baseline, levels of apoA-I increased in each sex, from the normotensive to prehypertensive and hypertensive group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…ApoA1 is usually considered as an anti-inflammatory and atheroprotective agent [ 24 ]. However, it was recently demonstrated that high ApoA1 levels could predict the development of prehypertension [ 25 ] and type-2 diabetes [ 26 ]. Presence of ApoA1 was also observed in amyloid deposit of knee joint menisci and in acute gouty arthritis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ApoA1 is usually considered as an anti-inflammatory and atheroprotective agent [ 24 ]. However, it was recently demonstrated that high ApoA1 levels could predict the development of prehypertension [ 25 ] and type-2 diabetes [ 26 ]. Presence of ApoA1 was also observed in amyloid deposit of knee joint menisci and in acute gouty arthritis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Onat et al . have also declared that ApoA1 could be converted into pro-inflammatory particles by aggregation to lipoprotein (a) Lp(a) [ 25 ]. They recently observed that low circulating Lp(a) associated with high ApoA1/HDL-C ratio were predicting factors for hypertriglyceridemic waist phenotype, which is considered as the core of the metabolic syndrome in impacting coronary heart disease risk [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of substantial fibrosis of the right atrium may well be a consequence of autoimmune activation, analogous to the gradual development of fibrosis in chronic steatohepatitis. Prolonged BP elevation mediated by the autoimmune process [ 48 ] may also contribute to myocardial hypertrophy and to atrial fibrosis leading to incident AF. In the future, 3-dimensional speckle tracking echocardiography may be helpful in detecting atrial fibrosis as well as ventricular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Such a constellation has been documented among a Turkish adult population as being associated with an elevated future risk of DM, 23 prehypertension 24 and CHD, 25 and moderately reduced levels of Lp(a) are associated with the MetS in humans. Korean women with the MetS were reported to have elevated MIF levels.…”
Section: A Working Hypothesis On the Mechanisms Of The Effects Of Lacmentioning
confidence: 99%
“…This process is determined by genetics and race and is driven by excess adiposity, MIF and Lp(a) levels and whether and to the extent to which autoimmune activation is involved. 24 In order to better elucidate the degree of the role of this maternal substrate, there is a need for future research directed at the analysis of the elements of oxidative stress during gestation, postpartum and lactation, as well as the association of these findings with subsequent cardiometabolic risk, in different ethnicities/races and population segments that are prone to impaired glucose tolerance or the MetS.…”
Section: A Working Hypothesis On the Mechanisms Of The Effects Of Lacmentioning
confidence: 99%